Implementation of Information Modelling Technology in Design of Structures of a Single-Storey Industrial Building - Marina A. Orlova; Sergey A. Kozyrev (Железобетонные конструкции)
Currently, much attention is paid to the structural reliability and safety of buildings and structures, as well as the speed and quality of design and construction. The increase in these indicators is facilitated by the expansion of the use of information modelling technology through the integration of new calculation methods into the digital building model.The paper considers the design of structures of a single-storey frame industrial building using information modeling technology. The order of work in the programs “Tekla Structures” and “Crystal” is presented on specific examples. Conclusions are given about the advantages of using BIM technologies in the construction industry.